2017
DOI: 10.2147/dddt.s125843
|View full text |Cite
|
Sign up to set email alerts
|

Protective influence of hyaluronic acid on focal adhesion kinase activity in human skin fibroblasts exposed to ethanol

Abstract: Aim The aim of this study was to evaluate the effect of ethanol and hyaluronic acid (HA) on cell survival and apoptosis in cultured human skin fibroblasts. Regarding the mechanism of ethanol action on human skin fibroblasts, we investigated cell viability and apoptosis, expression of focal adhesion kinase (FAK), and the influence of HA on those processes. Materials and methods Studies were conducted in confluent human skin fibroblast cultures that were treated with 25 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It has been reported that integrins play a key function in cell adhesion as signaling receptors, acting as a bridge between ECM and cytoskeleton proteins in order to allow cell movement [44,45]. Activation of the integrin complex (α1β1) by an extracellular ligand (e.g., collagen, laminin and elastin) leads to specific intracellular signaling, involving phosphorylation and dephosphorylation reactions for matrix remodeling [46,47]. Our results allowed us to evaluate a beneficial effect of the analyzed samples on proteins matrix hypothesizing an involvement of the integrins receptor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that integrins play a key function in cell adhesion as signaling receptors, acting as a bridge between ECM and cytoskeleton proteins in order to allow cell movement [44,45]. Activation of the integrin complex (α1β1) by an extracellular ligand (e.g., collagen, laminin and elastin) leads to specific intracellular signaling, involving phosphorylation and dephosphorylation reactions for matrix remodeling [46,47]. Our results allowed us to evaluate a beneficial effect of the analyzed samples on proteins matrix hypothesizing an involvement of the integrins receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Other anti-inflammatory compounds identified from our enrichment analysis in the current study, epigallocatechin gallate, valproic acid, quercetin, ketoconazole and acetaminophen have also been shown to suppress collagen and/or are anti-fibrotic in variety of tissues by yet to be elucidated mechanism [88][89][90][91][92]. Moreover, coffee and caffeine inhibit collagen expression and deposition, and have anti-fibrotic effects by blocking expressions and/or by modulating effects of profibrotic factors [93][94][95][96].…”
Section: Discussionmentioning
confidence: 76%
“…FAK is a non-receptor tyrosine kinase focal adaptor protein which is localized in integrin-focal sites [69] to link the growth factors and integrins [35]. The expression of FAK is induced either by direct effect of growth factors such as EGF [35] or by the action of extracellular signal-regulated kinase1/2 (ERK1/2) which is activated by EGF and HA stimulation [35, 43]. The active FAK induces the phosphatidylinositol 3-kinase (PI3K) expression [69], ultimately leading to the induction of the RAC1 and PAK family genes [70, 71].…”
Section: Discussionmentioning
confidence: 99%